Performing site-specific theatre : politics, place, practice - Birch, Anna; Tompkins, Joanne (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
Performing Site-Specific Theatre' turns a critical eye to the increasingly popular form of site-specific performance. By re-assessing this contemporary practice, the book investigates the nature of the relationship between 'site' and 'performance.' Site-specific performance operates differently from performance that takes place within a theatre venue because it seeks to match form and content (and place and space) more finely than does theatre that takes place inside conventional venues. Yet the form also encourages an investigation of how we might understand 'site' as less fixed or less specifically geographical; it broadens the types of relevant 'spaces' we might consider. The form also enables us to address a range of performative issues, from the development of site-specific 'soundscapes' to the role of the spectator in site-specific performance.
The 'place' and practice of site-specific theatre and performance / Joanne Tompkins -- Rethinking site-specificity: monopoly, urban space, and the cultural economics of site-specific performance / Michael McKinnie -- Rehearsing across space and place: rethinking A masque presented at Ludlow Castle / Susan Bennett, Julie Sanders -- Embodied presence and dislocated spaces: playing the audience in Ten thousand several doors in a promenade, site-specific performance of John Webster's The Duchess of Malfi / Jane Collins -- Haunted house: staging The Persians with the British Army / Mike Pearson -- Toiling, tolling, and telling: performing dissensus / Kathleen Irwin -- Beyond site-specificity: environmental heterocosms on the street / Susan Haedicke -- Repetition and performativity: site-specific performance and film as living monument / Anna Birch -- Contemporary ekkeklemas in site-specific performance / Lesley Ferris -- 'Place, like property prices, go up and down': site-specificity, regeneration,and The Margate exodus / Louise Owen -- Ambulatory audiences and animate sites: staging the spectator in site-specific performance / Keren Zaiontz -- Immersive negotiations: binaural perspectives on site-specific sound / Bruce Barton, Richard Windeyer -- My sites set on you: site-specificity and subjectivity in 'intimate theatre' / Helen Iball -- Siting the people: power, protest, and public space / Sophie Nield.
Bibliografija. - Kazalo
Keywords: Site-specific theater; izvedbene umjetnosti -- izvedbeni prostori; kazalište -- site-specific; prostorom određeno kazalište